2005
DOI: 10.1063/1.1872216
|View full text |Cite
|
Sign up to set email alerts
|

Efficient polymer-nanocrystal quantum-dot photodetectors

Abstract: We have realized highly efficient photodetectors based on composites of the semiconducting polymer poly͓2-methoxy-5-͑2Ј-ethylhexyloxy͒-1,4-phenylenevinylene͔ and PbSe nanocrystal quantum dots. The external quantum efficiency in these devices is greater than 1 for electric fields E ϳ 7 ϫ 10 5 V / cm. The observed photocurrent gain could be attributed to the carrier multiplication in PbSe nanocrystal quantum dots via multiple exciton generation, and the efficient charge conduction through the host polymer materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
100
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(104 citation statements)
references
References 11 publications
2
100
0
2
Order By: Relevance
“…One approach is to use all of the available energy of high-energy photons by generating multiple excitons from a single absorbed photon. Ellingson et al (85) reported multiple exciton generation by using PbSe and PbS quantum dots; Qi et al (86) have also reported similar results with polymer-quantum dot blends (86). The ability to capture and use all of the energy from a highenergy photon greatly improves the overall energy efficiency of solar energy conversion.…”
Section: Opportunities For Nanotechnology: Synthetic and Biomimetic Asupporting
confidence: 51%
“…One approach is to use all of the available energy of high-energy photons by generating multiple excitons from a single absorbed photon. Ellingson et al (85) reported multiple exciton generation by using PbSe and PbS quantum dots; Qi et al (86) have also reported similar results with polymer-quantum dot blends (86). The ability to capture and use all of the energy from a highenergy photon greatly improves the overall energy efficiency of solar energy conversion.…”
Section: Opportunities For Nanotechnology: Synthetic and Biomimetic Asupporting
confidence: 51%
“…Using the size effect, the optical absorption and emission spectra of the nanocrystals can further be conveniently tuned. These make nanocrystals attractive for use in different optoelectronic device applications including LEDs [11,12], hybrid white light sources [13], photovoltaic cells [14], photodetectors [15] and optical memories [16]. However, the applications of nanocrystals are not limited only to such devices.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the QDs used in UV-PDs are binary systems, the band gap of which are tuned by varying the diameter of the nanoparticle [1][2][3][4][5]7,8,16]. However in ternary QDs, the band gap may be tuned by the relative composition of materials used as well [6,17].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, due to the possibility to change the photo physical properties through simplified chemical synthesis and easy thin film processing, quantum dots (QD) and polymer:QD hybrids attract a lot of attention in UV-PD applications [1][2][3][4][5][6][7][8], as well as the other photonic applications, such as biological imaging and contrast agents [9,10], light-emitting devices (LEDs) [11,12] photovoltaic [13][14][15], etc. Most of the QDs used in UV-PDs are binary systems, the band gap of which are tuned by varying the diameter of the nanoparticle [1][2][3][4][5]7,8,16].…”
Section: Introductionmentioning
confidence: 99%